1973
DOI: 10.1017/s0003356100017141
|View full text |Cite
|
Sign up to set email alerts
|

A note on the digestibility by sheep of hulls from the field bean (vicia faba l)

Abstract: The digestibility of a feed containing hull material prepared mechanically from Throws MS field bean (Viciafaba L) was determined in a 12-day balance trial with sheep. The pelleted feed contained 62 % hulls and 38 % of a concentrate mixture, and was given at a maintenance level. The mean digestibility coefficients of the feed were for dry matter, 66-3; organic matter, 68-2; nitrogen, 65-7; crude fibre, 59-4; and energy, 65-5%. The coefficients for the bean hulls themselves, estimated by assuming coefficients f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1974
1974
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The digestibility of hulls of grain legumes appears to be much higher than for cereal grains. Edwards et al (1973) and Rowe & Hargreave (1988) reported digestibilities of 0.60-0.62 for the organic matter, N and fibre components of faba beans and lupin grain, these values possibly reflecting the low lignin content of this material.…”
Section: F E R M E N T a T I O N I N T H E R U M E Nmentioning
confidence: 96%
“…The digestibility of hulls of grain legumes appears to be much higher than for cereal grains. Edwards et al (1973) and Rowe & Hargreave (1988) reported digestibilities of 0.60-0.62 for the organic matter, N and fibre components of faba beans and lupin grain, these values possibly reflecting the low lignin content of this material.…”
Section: F E R M E N T a T I O N I N T H E R U M E Nmentioning
confidence: 96%
“…Composition of faba bean husks[16,19,45,[124][125][126][127][128][129][130][131][132][133][134][135][136][137]. All values given as g kg −1 DM (n number of observations, SD standard deviation)…”
mentioning
confidence: 99%